The power spectrum in a strongly inhomogenous universe - Sylos Labini, Francesco; Amendola, Luca (The astrophysical journal. Part 2, Letters, 1996)
The standard picture of the matter clustering, the cold dark matter model (and its variants), assumes that, on scales smaller than a certain "flattening scale" λ f , the power spectrum increases with the scale, while on much larger scales it decreases so as to match the tiny fluctuations observed in the microwave background. However, there is no consensus on whether the turnaround λ f has been detected or not, and on the actual importance of the luminosity segregation effect. We show that, due to the finiteness of the sample, the standard analysis applied to fractal distributions yields a turnaround for scales close to the survey scale, and a systematic amplitude shift with the survey scale. We point out that both features, bending and scaling, are in agreement with recent determinations of the power spectrum, in particular with the CfA2 spectrum in redshift space. Therefore, our conclusion is that the CfA2 sample is consistent with a fractal clustering.